Changes of quality in agricultural drainage water between nature’s seasons - Stankevičienė, Rasa (International Conference “Environmental Engineering”, 2023)
Agricultural drainage and related water management systems are implemented to improve farming. Get higher yields of agricultural production. Remove excess water. When removing excess water in cultivated areas, it is important to reduce the leaching of polluting substances flowing out with drainage water throughout the year and in different seasons. Also ensure the safe and sustainable use of plant protection products and fertilizers. One of the possible solutions is to transform the old free drainage systems into controlled drainage systems. In such systems, it is possible to regulate the groundwater level in different seasons and according to the needs of the plants. In this way, to reduce the leaching of materials with drainage water. This article presents an analysis of controlled and free drainage water pollution in separate seasons. Researches were carried out in Pasvalys district, where both types of drainage systems operate next to each other.